True triaxial test and PFC3D-GBM simulation study on mechanical properties and fracture evolution mechanisms of rock under high stresses. (February 2023) - Zheng, Zhi; Tang, Hao; Zhang, Qiang; Pan, Pengzhi; Zhang, Xiwei; Mei, Guoxiong; Liu, Zaobao; Wang, Wei
Abstract: After the excavation of deep underground engineering, the complex 3D high-stress redistribution occurs in the surrounding rock, resulting in deterioration of mechanical properties of surrounding rock and even strong brittle failure and catastrophe. However, the micromechanical mechanisms are not clear. Therefore, in this study, true triaxial laboratory tests and PFC3D numerical simulations are conducted on deeply buried marble, and a new 3D-GBM numerical model method incorporating the mineral composition and grain size distribution characteristics of the marble and considering the contacts between and within mineral grains was proposed. The pre- and post-deformation, strength, macro- and micro-fracture characteristics, fracture evolution processes and tensile–shear fracture mechanisms of marble under different σ 2 and σ 3 were systematically investigated. In particular, the effects of σ 2 and σ 3 on the intergranular and transgranular micro-failure of mineral grains were analyzed; the microcrack anisotropic characteristics, microcrack propagation processes and tensile–shear mechanisms induced by true triaxial stresses ( σ 2, σ 3 ) were further studied; and the AE parameter b -value and magnitude M were realized in the proposed 3D-GBM to study the precursor characteristics of marble failure. Finally, the effects of the mineral grain size, particle number and specimen size on the mechanical properties and micro-failure mechanisms of marble were further explored.